Bowl versus Funnel Supramolecular Concept for CuI Complexes within the Biomimetic Tris(imidazole) Core. Issue 29 (21st August 2013) - Gout, Jérôme; Višnjevac, Aleksandar; Rat, Stéphanie; Bistri, Olivia; Le Poul, Nicolas; Le Mest, Yves; Reinaud, Olivia
Abstract: The coordination of Cu I to a poly(imidazole) core is of the most importance in biology as it is present in most enzymes as well as in peptides involved in pathological processes. Here, we report a detailed study of the binding of Cu I to a tris(imidazole) core constructed on a resorcinarene scaffold. NMR and IR spectroscopy as well as cyclic voltammetry have been used to characterize the different species obtained in solution as a function of the presence or absence of exogenous ligands, mainly CO and MeCN, but also Cl – . Within the resorcinarene scaffold, the metal ion can switch from a dynamic two‐coordinate to a four‐coordinate environment upon binding to a π acceptor. A comparison with previously reported calix[6]arene‐based tris(imidazole) Cu complexes highlights several key points: (1) the importance of the shape and size of the macrocycle that forms the pocket in which the metal center is partly embedded, (2) the importance of the flexibility of the system as it undergoes induced‐fit processes (calixarene) or not (resorcinarene), (3) the consequences on the affinity of the metal center for CO and MeCN in relation to its π‐backbonding capabilities, and finally (4), the redox behavior of the system. Abstract : A resorcinarene‐based tris(imidazole) ligand provides a supramolecular environment with different shape, rigidity, and binding properties to those provided by a calix[6]arene‐based ligand. The differences are highlighted with MeCN, CO, and Cl – guest ligands.